2011
DOI: 10.1016/j.ijhydene.2011.08.065
|View full text |Cite
|
Sign up to set email alerts
|

Ignition characteristics of heptane–hydrogen and heptane–methane fuel blends at elevated pressures

Abstract: There is significant interest in using hydrogen and natural gas for enhancing the performance of diesel engines. We report herein a numerical investigation on the ignition of n-C 7 H 16 /H 2 and n-C 7 H 16 /CH 4 fuel blends. The CHEMKIN 4.1 software is used to model ignition in a closed homogenous reactor under conditions relevant to diesel/HCCI engines. Three reaction mechanisms used are (i) NIST mechanism involving 203 species and 1463 reactions, (ii) Dryer mechanism with 116 species and 754 reactions, and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(27 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Many researchers have also studied the effects of adding hydrogen to hydrocarbon fuels via sensitivity analyses [47,48]. Fig.…”
Section: Chemical Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have also studied the effects of adding hydrogen to hydrocarbon fuels via sensitivity analyses [47,48]. Fig.…”
Section: Chemical Kineticsmentioning
confidence: 99%
“…It has been widely reported [32,48] that the increase in the ignition delay at low temperatures is primarily caused by the following reaction:…”
Section: Chemical Kineticsmentioning
confidence: 99%
“…For instance, by utilizing the proposed approach, the size of the comprehensive mechanism of n-heptane (561 species and 2539 reactions) reduced to only 140 species and 491 reactions. Aggarwal et al [19] investigated the ignition characteristics of n-heptane/ methane fuel blends at HCCI engines condition in a closed homogenous reactor. They showed that the Chalmers reduced mechanism [18], consisting of 42 species and 168 reactions, has good agreement with the shock tube data for the mixtures of pure n-heptane/air and also for the mixture of pure methane/air.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental and practical aspects of the usage of hydrogen-hydrocarbon mixtures on both transportation and power generation (in terms of their mechanical and chemical properties) in different systems, such as engines [11][12][13][14][15][16][17][18][19][20][21][22][23][24], burners [25][26][27][28][29][30][31][32][33][34], combustion bombs [35][36][37][38][39][40][41], vessels [8,9,[42][43][44][45][46] and chambers [5,10,[47][48][49][50][51][52][53][54], have been broadly investigated. The parameters affecting hydrogen-hydrocarbon mixtures have been studied, including flame configurations, e.g., laminar premixed …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for the diffusion of combustion, hydrogen-enrichments can suppress the formation of soot particles [72,90] and reduce ignition delay [6,26,53,91].…”
Section: Introductionmentioning
confidence: 99%